Performance improvement of spectral amplitude coding-optical code division multiple access systems using NAND detection with enhanced double weight code - Nasim, Ahmed; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; R. Badlishah, Ahmad, Assoc. Prof. Dr. (The Optical Society of Japan, 2012)
Link to publisher's homepage at http://annex.jsap.or.jp/OSJ/index-e.shtml